Lincoln in the world : the making of a statesman and the dawn of American power - Peraino, Kevin (New York : Crown Publishers, an imprint of the Crown Publishers Group, a division of Random House LLC, a Penguin Random House Company, 2013)
A study of the sixteenth president's evolution as a foreign policy leader explores his role in America's rise to a world power, analyzing six distinct episodes that defined his foreign policy stance and enabled him to maintain a careful balance during the war years.
Lincoln vs. Herndon -- Lincoln vs. Seward -- Lincoln vs. Palmerston -- Lincoln vs. Marx -- Lincoln vs. Napoleon -- Lincoln vs. Lincoln.
Includes bibliographical references (pages 387-406) and index.
Keywords: United States -- Foreign relations -- 1861-1865.; Lincoln, Abraham, -- 1809-1865.; Statesmen -- United States